Quantitative profiling and mechanisms exploration of Epimedium total flavonoid capsules in neuroinflammation: An integrated study of pharmacokinetics, network pharmacology, and molecular pathways - Xiaochun Zeng; Junran Shao; Dabo Pan; Siying Zeng; Zhenzhong Wang; Xinsheng Yao; Haibo Li; Wei Xiao; Yang Yu (Arabian Journal of Chemistry)
Epimedium total flavonoid capsules (ETFCs), a traditional Chinese patent medicine derived from Epimedium brevicornu Maxim., have been used for centuries to treat primary osteoporosis and are associated with kidney yang deficiency symptoms. Based on the “kidney-brain axis” hypothesis, previous study demonstrated that ETFCs can improve the cognitive function of MCAO rats, and the mechanism may involve the inflammatory response. However, little is known about their therapeutic components and scientific connotations. This study systematically investigates the anti-neuroinflammatory material basis and the mechanisms of ETFCs, integrating UPLC-Q/TOF-MS and UPLC-TQ-MS for chemical profiling, quantitative analysis of key components in rats′ plasma and brain, along with network pharmacology and activity verification. As a result, 65 components were identified. Metabolite profiling showed a total of 130 xenobiotics, highlighting the extensive metabolic transformations. Pharmacokinetic studies showed that primary flavonoid glycosides were quickly absorbed, while secondary glycosides exhibited slower absorption and elimination. In brain tissue, both prototype glycosides and secondary glycosides reached their peak concentrations rapidly, with Tmax between 0.25–1 h, while the prototype glycosides were eliminated after 8 h and secondary glycosides exhibited a secondary peak at 6–8 h. A network pharmacology study revealed that prototypes in blood may play a therapeutic role through targets including AKR1B1, PDE5A, and PTGS2 (COX-2). The LPS-induced BV-2 cell model confirmed ETFCs′ constituents showed inhibitory activities on pro-inflammatory cytokine secretion, mRNA expressions of IL-6, TNF-α, COX-2, iNOS and could down-regulate the protein expressions of COX-2 and iNOS. This research lays the foundation for the further development and utilization of ETFCs.